The effects of oxygen stresses on the development of features of severe retinopathy of prematurity: knowledge from the 50/10 OIR model - Elizabeth Hartnett, M. (Documenta ophthalmologica, 2010)
The objective of this study is to determine growth factor expression and activation of signaling pathways associated with intravitreous neovascularization and peripheral avascular retina using a model of retinopathy of prematurity (ROP) relevant to today with oxygen monitoring in neonatal units. Studies using 50/10 oxygen-induced retinopathy (OIR) and 50/10 OIR+SO models were reviewed. Repeated fluctuations in oxygen increased retinal vascular endothelial growth factor (VEGF) even while peripheral avascular retina persisted and prior to the development of intravitreous neovascularization. Repeated fluctuations in oxygen increased VEGF 164 expression but not VEGF 120 . Neutralizing VEGF bioactivity significantly reduced intravitreous neovascularization and arteriolar tortuosity without interfering with ongoing retinal vascularization. Repeated oxygen fluctuations led to retinal hypoxia and increased reactive oxygen species (ROS). Inhibiting ROS with NADPH oxidase inhibitor, apocynin, reduced avascular retina by interfering with apoptosis. Supplemental oxygen reduced retinal VEGF concentration and exacerbated NADPH oxidase activation to contribute to intravitreous neovascularization through activation of the JAK/STAT pathway. Oxygen stresses relevant to those experienced by preterm infants today trigger signaling of different pathways to cause avascular retina and intravitreous neovascularization. Increased signaling of VEGF appears important to the development of both avascular retina and intravitreous neovascularization.